IMF Committee on Balance of Payments Statistics : Annual Report 2008. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2010)
This report constitutes the annual report of the IMF Committee on Balance of Payments Statistics (Committee). The Committee, which held its annual meeting at the European Central Bank (ECB) in Frankfurt, Germany, in October 2008, was established in 1992 to improve the availability, consistency, and reliability of balance of payments and international investment position statistics worldwide. This annual report provides an overview of recent trends in balance of payments and international investment position statistics, discusses the Committee's work program during 2008, and reviews the issues the Committee plans to address in the coming year.